Continuing recovery of wolves in Europe ... - Di Bernardi, Cecilia; Chapron, Guillaume; Kaczensky, Petra; Álvares, Francisco; Andrén, Henrik; Balys, Vaidas; Blanco, Juan Carlos; Chiriac, Silviu; Ćirović, Duško; Drouet-Hoguet, Nolwenn; Huber, Djuro; Iliopoulos, Yorgos; et al. (Dryad, 2025)
The recovery of wolves (Canis lupus) across Europe is a notable conservation success in a region with extensive human alteration of landscapes and high human population densities. We provide a comprehensive update on wolf populations in Europe, estimated at over 21,500 individuals by 2022, representing a 58% increase over the past decade. Despite the challenges of high human densities and significant land use for agriculture, industry, and urbanization, wolves have demonstrated remarkable adaptability and increasing population trends in most European countries. Improved monitoring techniques, although varying in quality and scope, have played a crucial role in tracking this recovery. Annually, wolves kill approximately 56,000 domestic animals in the EU, a risk unevenly distributed and differently handled across regions. Damage compensation costs 17 million EUR every year to European countries. Positive economic impacts from wolf presence, such as those related to reducing traffic accidents with wild ... : In fall 2022, the authors of this paper compiled estimates of wolf population size, trends and damages within their country, as well as details of the monitoring methodology used, the quality of the data, and other information on the legal status and main conservation measures, following a similar method as Chapron et al. (2014), restricting the compilation to existing information and without new analyses of raw monitoring data. Information was obtained from the most reliable sources available at the national level. This joint compilation effort was facilitated by the Large Carnivore Initiative for Europe, a Specialist Group of the IUCN’s Species Survival Commission. Collectively we covered all the European continent, except for the Russian Federation, Belarus and the Republic of Moldova, representing 34 countries (Albania, Austria, Belgium, Bosnia & Herzegovina, Bulgaria, Croatia, Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Hungary, Italy, Kosovo, Latvia, Lithuania, Luxembourg, ...